Analysis of ethylene biosynthesis gene expression profile during titanium dioxide (TiO2) treatment to develop a new banana postharvest technology - Rizkita R Esyanti; Veinardi Suendo; Aksarani ‘Sa Pratiwi; Fenny M Dwivany; Annisa A Putri (Indonesian Journal of Biotechnology, 2019)
Banana is an important crop that demands proper methods in postharvest handling. As a climacteric fruit, thebanana fruit ripening process is aﬀected by ethylene. Several methods have been developed to extend the shelf life of a banana, such as using ethylene scrubbers. In this study, ttanium dioxide (TiO2), a photocatalyst, was used as an alternatve method to delay the fruit ripening process. The eﬀect of TiO2 on the ripening‐related gene MaACS1 was investgated. Banana fruits were placed in a TiO2‐coated glass chamber and observed for ten days. Fruit ripening in the treated chamber was delayed for eight days compared to the control. Total RNA was extracted from control and TiO2‐treated fruit pulp and synthesized into cDNA. Reverse transcripton PCR was performed to investgate the gene expression, which showed that MaACS1 expression was relatvely lower than treated control. The fnding of these studies suggested that the TiO2 chamber has the potental to extend the shelf life of banana by delaying its ripening process and decreasing the expression of MaACS1. To the best of our knowledge, no previous study has investgated the eﬀect of TiO2 on the expression of genes related to banana fruit ripening.